2005
DOI: 10.1111/j.1939-1676.2005.tb02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base and Electrolyte Abnormalities in Dogs with Gastrointestinal Foreign Bodies

Abstract: Gastrointestinal foreign bodies occur commonly in dogs. The objective of the study was to describe the acid-base and electrolyte abnormalities identified in dogs with gastrointestinal foreign bodies and determine if these abnormalities are related to the site or type of foreign body present. Medical records of 138 dogs were reviewed, and information on signalment, initial venous electrolyte and acid-base values, surgical findings, relevant historical information, imaging modalities used, cost of hospital visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 15 publications
(14 reference statements)
11
81
1
5
Order By: Relevance
“…Reported survival rates of dogs undergoing surgery of the gastrointestinal tract vary from 80 to 99% (Evans et al , Boag et al , Shales et al , Hayes ), with the present study results being 96% for both groups. However, it should be noted that the current study was unable to provide follow‐up past the time of discharge for all patients, and it is therefore difficult to directly compare survival rates with other studies.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Reported survival rates of dogs undergoing surgery of the gastrointestinal tract vary from 80 to 99% (Evans et al , Boag et al , Shales et al , Hayes ), with the present study results being 96% for both groups. However, it should be noted that the current study was unable to provide follow‐up past the time of discharge for all patients, and it is therefore difficult to directly compare survival rates with other studies.…”
Section: Discussionsupporting
confidence: 50%
“…Hypochloraemia, metabolic alkalosis, hypokalaemia and hyponatraemia have been reported in dogs with various gastrointestinal foreign bodies, with LFB being more likely associated with hyponatraemia (Boag et al ). Similarly, the present study demonstrated that dogs with LFB were more likely to have lower sodium, potassium and chloride concentrations, but also demonstrated haemoconcentration, an increase in blood urea nitrogen concentrations, and higher pH than dogs with NLFB.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal obstruction results in disturbances of fluid balance, acid‐base status and serum electrolyte concentrations due to hypersecretion and sequestration within the gastrointestinal tract which is exacerbated by vomiting and impaired oral intake of fluid and nutrients (Boag and others 2005). Gastrointestinal foreign bodies may cause complete or partial obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Hypochloraemic metabolic alkalosis is common in dogs with GI foreign bodies and functional pyloric outflow obstruction. 10 In a recent study examining metabolic alkalosis in dogs and cats, 87% of cats with a metabolic alkalosis were hypochloraemic. 1 In an experimental study of complete obstruction of the ileum in dogs, it was found that bowel proximal to obstruction had net water, sodium and potassium secretion (chloride was not measured), resulting in sequestration of fluid and electrolytes into the lumen of the intestine.…”
Section: Discussionmentioning
confidence: 99%